2019
DOI: 10.1111/trf.15444
|View full text |Cite
|
Sign up to set email alerts
|

Usutu virus infection in Dutch blood donors

Abstract: BACKGROUND The screening of Dutch blood donations for West Nile virus (WNV) may be imminent, as WNV emerges in nearby countries and more donors travel to WNV‐affected regions. Since 2016 the related, mosquito‐borne Usutu virus (USUV) causes seasonal mortality in Dutch birds. To what extent will human USUV infections affect Dutch WNV donor screening? STUDY DESIGN AND METHODS From April through September 2018, plasma samples from blood donations in blackbird‐rich regions were stored. When increased bird mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…Studies revealed an increase of USUV seroprevalence in northern Italy [25][26][27], especially among forest rangers [28]. In the present study, an increasing number of USUV and WNV cases was reported, in line with other European studies [18,[29][30][31][32].…”
Section: Discussionsupporting
confidence: 91%
“…Studies revealed an increase of USUV seroprevalence in northern Italy [25][26][27], especially among forest rangers [28]. In the present study, an increasing number of USUV and WNV cases was reported, in line with other European studies [18,[29][30][31][32].…”
Section: Discussionsupporting
confidence: 91%
“…In Europe, the recent epizootics were also accompanied by several descriptions of human neurological disorders, including facial paralysis, encephalitis, meningitis and meningoencephalitis, in immunocompromised and immunocompetent patients, representing to date around 30 cases [7,[18][19][20][21][22][23][24][25]. Moreover, molecular and serologic evidence of USUV infection in Italian, German, Austrian and Dutch blood donors indicates that the virus is also circulating silently among asymptomatic humans in Europe and could potentially be a concern PLOS NEGLECTED TROPICAL DISEASES for blood transfusions [26][27][28][29]. Very little is known about USUV pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…The circulation of USUV in birds can be linked to an increased human exposure to zoonotic risk. Indeed, the detection of viremic blood donations in the Netherlands co-incided with months of active USUV circulation in birds 22 , human cases described in Italy were from an area with demonstrated concomitant circulation of USUV in mosquitoes and birds [16][17][18][19] , and in Austria an increase in human cases was observed alongside the increased USUV activity in birds 23 .…”
mentioning
confidence: 99%